Montreal Jewish Day School teachers’ real-time experiences during Covid-19 online distance learning - Thurber, Lauren; Hirsch, Sivane; Feldman, Devorah (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2025)
During the Covid-19 pandemic, Montreal Jewish Day Schools shifted to online distance learning. This study follows eight elementary and high school teachers in real-time through observations and group interviews. Applying a Community of Inquiry framework, we unpack the social, conceptual, and pedagogical elements of this pedagogical shift to understand its three “modes”: survival, transition, and innovation, distinguished by stability and connectivity. Peer-to-peer and student-teacher connectivity was mostly underdeveloped and fostered feelings of disappointment and frustration. Teachers varied in their engagement with specific Judaic traditions within their online classrooms and relied on school-wide resources to sustain Jewish identity connectivity for students. The ever-changing timeline of the shifts in conjunction with personally- and community- attributed pressures contributed to teachers’ experiences of anxiety.